Blackbody radiation shift assessment for a lutetium ion clock - K. J. Arnold (Nature Portfolio, 2018)
There is a continuous effort to improve the accuracy of atomic clocks. Here the authors measure the static differential scalar polarizability of Lutetium ion resonant transitions and its lower light shift from blackbody radiation makes it a promising candidate for ion-based atomic clocks.